Rancang Bangun Website Profil Desa Manik Maraja Sebagai Media Informasi Digital - Indriani Aulia Rahmadani; Mohammad Yusup; Supiyandi (Jurnal Nasional Teknologi Komputer, 2026)
In the context of globalization, the advancement of information technology necessitates enhanced efficiency in managing data, particularly within village governance. Manik Maraja Village continues to depend on traditional methods, such as bulletin boards, banners, and oral communication, leading to inadequate dissemination of information and restricted access for the public to current updates. This research endeavors to create and develop a web-based village information system that supports effective and transparent management and distribution of data. The approaches applied involve collecting data through observation, interviews, and literature review, coupled with the use of the Waterfall model for system development. The system incorporates features like village profiles, news, event schedules, and other details that can be accessed instantly by the community. The adoption of this technology is projected to foster digital transformation at the village administration level, boost community engagement, and offer solutions to the complexities of information handling in the digital age.